Long-term fermented organic fertilizer application reduce urea nitrogen-15 loss from plastic shed agricultural soils - Hou Maomao; Tang Songyan; Zhu Qinyuan; Chen Jingnan; Xiao Ying; Jin Qiu; Zhong Fenglin (Annals of Agricultural Sciences, 2023)
Continuous application of fermented organic fertilizer can improve soil quality, while the performance of nitrogen (N) in the improved soils is rarely investigated. To investigate the fate of applied N in the soils with organic management history, the 15NH2CO15NH2 (15N abundance of 19.6 %) was employed as the exogenous N source to conduct an experiment in the Chinese cabbage and tomato rotation system under plastic shed condition. The cultivated soils have received 15-year of effective microorganism (EM) fermented organic fertilizer (EM-OF), N, P, K inorganic fertilizer (NPK-IF) and no fertilizer (NoF). The 15N use by cabbage and tomato, the soil 15N forms, as well as the 15N distribution were observed. Results showed that the 15N use efficiency of cabbage in the EM-OF, NPK-IF and NoF soils were 55.1 %, 37.3 % and 26.6 % respectively, showing significant (p ≤ 0.05) differences. The succeeding crop tomato could take up the soil residual 15N, and the highest 15N reuse efficiency was 7.1 % that detected in the NoF soil. The total 15N loss (6.0 %) from the rotation system was the lowest in the EM-OF soil, compared to that in the NPK-IF and NoF soils. It was concluded that the long-term fermented organic fertilizer applied soils can reduce urea 15N loss from plastic shed agriculture, mainly through improving the in-season crop 15N use efficiency.